The temporal evolution of family educational priorities and their impact on children’s sports participation: evidence from the HAPC model - Zong, Yanwei; Li, Aihong; Wang, Shoudu (Frontiers in Psychology, 2025)
IntroductionThis study examines how family educational priorities influence children’s sports participation in China. Drawing on social learning theory and ecological systems theory, it conceptualizes parental emphasis on education as a proximal environmental factor shaping children’s behavioral development through modeling, reinforcement, and value transmission.MethodsUsing nationally representative data from the China Family Panel Studies (CFPS) spanning 2014–2020, the analysis applies a Hierarchical Age-Period-Cohort (HAPC) model to estimate the effects of parental educational emphasis on the frequency and duration of children’s physical activity.ResultsThe findings show that stronger parental emphasis on education is positively associated with both the frequency and duration of children’s physical activity. A generational turning point is identified around the 1980 birth cohort, where the impact of parental educational focus shifts from negative to positive. Heterogeneity analysis further indicates that the positive association is more pronounced in urban, two-parent households and among boys.DiscussionThese results highlight the evolving psychological and social mechanisms by which family education priorities shape children’s motivation and participation in physical activity. The findings provide policy-relevant insights for designing equitable, psychologically grounded strategies to promote youth development and reduce disparities in sports participation.